Flashmobs as Performance and the Re-emergence of Creative Communities - Aristita Ioana Albacan (University of Hull – Scarborough, United Kingdom) (Revista Brasileira de Estudos da Presença, 2013)
In spite of their very brief history – the first modern flashmob took place at Macy’s in NY, on the evening of 17th of June 2003 – flashmobs have rapidly spread throughout the Western world, developing in recent years into a particularly novel mode of performance that stimulates the re-emergence – even if temporary and fleeting – of creative communities, whilst responding to a range of topics of societal currency: political, cultural, artistic, everyday life etc. Flashmobs become visible within the public sphere via short, exciting performative acts perceived as playful and liberating. In processual terms, flashmobs as performances pertaining to a globalized, neo-liberal cultural economy, hybridize conventions and practices from live, online, and mobile media in novel, unprecedented ways.